Damage and Fracture of Composite Materials and Structures - Tamin, Mohd Nasir; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2012)
This monograph presents recent research findings on fracture properties and behavior of the composites, and their damage and cracking process under both quasi-static and impact loading conditions. Theoretical treatment, experimental investigation and numerical simulation aspects of the mechanics of composites, including sandwich structures are included.
Introduction -- Mode-I Crack Control by SMA Fiber with a Special -- The Study of Response of High Performance Fibers-Reinforced Composites to Impact Loading -- Indentation of Sandwich Beams with Functionally Graded Skins and Transversely Flexible Core -- Micromechanical Fibre-Recruitment Model of Liquid Crystalline Polymer Reinforcing Polycarbonate Composites -- Modeling of Spalling Effect on Toughening in Fiber Reinforced Composites -- Evolution Characteristics of Delamination Damage in CFRP Composites under Transverse Loading -- Dynamic Fracture Toughness of Composite Materials -- Micromechanical Analysis of Mode I Crack Growth in Carbon Fibre reinforced Polymers -- Experimental and Simulation of Composite Structure Subjected to Impact Loading.-Blast Response of Fibre Reinforced Composites and Sandwich Structures -- Closure.
Keywords: Engineering; Computer science; Materials; Surfaces (Physics).; Engineering; Continuum Mechanics and Mechanics of Materials; Characterization and Evaluation of Materials; Computational Science and Engineering; Ceramics, Glass, Composites, Natural Methods